2019
DOI: 10.1177/0361198119838982
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion on Dockless Bike Sharing: A Machine Learning Approach

Abstract: Dockless bike sharing is an emerging paradigm. Like many other technologies, it brings advantages and disadvantages to communities. Further investigation into public opinion will shed light on the impact of this technology on communities and provide input to city authorities for transportation planning. Transportation planning processes can be enhanced by engaging the community through social media technologies. Social media like Twitter, Facebook, and other microblogging media have been used for planning, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…This study also reported that peer-to-peer sharing is likely to remain a niche with special purpose bikes. In dock-based schemes, satisfaction is flawed by a set of factors such as the mechanics of the bikes, the picking and dropping system, and the apps used to organise the service [34], while dockless shared mobility models are potentially useful in generating participation but face substantial technical, analytical, and communication barriers [35]. The rapid expansion of dockless bike-sharing may be the reason behind a large-scale renaissance of the very concept since 2016, however, this is coincident with the serious oversupply of bikes [36] in many programmes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study also reported that peer-to-peer sharing is likely to remain a niche with special purpose bikes. In dock-based schemes, satisfaction is flawed by a set of factors such as the mechanics of the bikes, the picking and dropping system, and the apps used to organise the service [34], while dockless shared mobility models are potentially useful in generating participation but face substantial technical, analytical, and communication barriers [35]. The rapid expansion of dockless bike-sharing may be the reason behind a large-scale renaissance of the very concept since 2016, however, this is coincident with the serious oversupply of bikes [36] in many programmes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, in dockbased schemes satisfaction is seriously affected by a set of factors like the mechanics of the bikes, the picking and dropping system, and the apps used to organise the service (Manzi and Saiben, 2018). At the same time dockless shared mobility models are potentially useful in generating participation, but face substantial technical, analytical, and communication barriers (Taleqani, et al, 2019) and higher vulnerability to mismanagement (Luo et al, 2019).…”
Section: Dockless Bike Sharing Systems: a Brief Reviewmentioning
confidence: 99%
“…For example, natural language processing tools can identify geo-localized urban activities from publicly available text obtained from, e.g. Twitter (Rahim Taleqani, Hough, & Nygard, 2019), where location information can be extracted and associated to activities of relevance.…”
Section: Generating Climate Semanticsmentioning
confidence: 99%